Entrepreneurs’ Specific Value Orientations into the Business-Family Sphere - MURZINA, JULIA SERGEEVNA; POZNIAKOV, VLADIMIR PETROVICH; MENSH, ELENA ALEXANDROVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article is devoted to the study of the specific value orientations of Russian entrepreneurs concerning their families and business. Finally, 93 values were identified. Terminal values turned out to be more differentiated in the sphere of business; family values had undivided meanings, and merged with the self-image. An analysis of the instrumental values of family and business showed that they repeat each other by a quarter; otherwise, they were subject-specific. The article proposes a projective technique: the proprietary structure of in-depth interviews, based on prototypical situations that are symmetrical in the life cycle of an organization and a family. RESUMEN Este artículo está dedicado al estudio de las orientaciones específicas de valores de los empresarios rusos con respecto a sus familias y negocios. Finalmente, se identificaron 93 valores. Los valores terminales resultaron ser más diferenciados en el ámbito de los negocios; los valores familiares tenían significados no divisibles y se fusionaban con la autoimagen. Un análisis de los valores instrumentales de la familia y la empresa mostró que se repiten en una cuarta parte; de otra manera, serían específicos del tema. El artículo propone una técnica proyectiva: la estructura propia de las entrevistas en profundidad, basada en situaciones prototípicas que son simétricas en el ciclo de vida de una organización y una familia.